The Power of Belief: How Ethnocentrism, Religion, and Brand Importance Shape Boycott Behavior and Brand Perceptions in Indonesia - Stella Kusmayadi (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose: This study aims to understand the role of boycott intention in mediating the effects of consumer ethnocentrism, religious animosity, legitimacy, and brand importance on brand image, loyalty, and product judgment among Starbucks consumers in Indonesia.Method: This study was conducted using quantitative methods to test the proposed theoretical model. Online questionnaires were distributed to 406 respondents to measure several variables, including consumer ethnocentrism, religious animosity, legitimacy, brand importance, boycott intention, boycott behavior, brand image, loyalty, and product judgment. The data were collected cross-sectionally from Starbucks consumers in Indonesia. The data analysis method used was Partial Least Squares Structural Equation Modeling (PLS-SEM).Result: This study shows that the indirect relationships from consumer ethnocentrism, religious animosity, and legitimacy to boycott behavior, through boycott intention, have a negative effect. In contrast, the indirect relationship from brand importance to boycott behavior, through boycott intention, has a positive effect. Specifically, the higher the levels of consumer ethnocentrism, animosity, and legitimacy, the higher the boycott intention. This suggests that consumers in Indonesia who strongly identify with moral, cultural, and religious solidarity are more likely to have an intention to boycott.Practical Implications for Economic Growth and Development: This study provides insights for companies on how to develop transparent and responsive communication strategies to address issues that may trigger boycott intentions.